An Estimate on Distribution of Hysteretic Energy Demand in Seismic Precast Concrete Frame Structures - Du, Bin; He, Zheng; Huang, Guohui (Journal of earthquake engineering : JEE, 2021)
New procedures are proposed for estimating the hysteretic energy demand distribution of precast concrete frames using the shear-bending story model and energy spectra. An efficient beam element is specifically developed to account for the effects of some precast connection parameters. The rationality of the proposed procedures is systematically demonstrated. The distribution of hysteretic energy demand is found to be closely related to the type, location and stiffness of connections. It is feasible to utilize the relationships between the hysteretic energy demand distribution and connection parameters to achieve an optimal energy-based seismic design for minimizing structural damage.